Phosphoric acid-in-clay electrolyte boosting polybenzimidazole membranes for high performance fuel cells - Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Nanwen Li; Jun Yang (2025)
The development of phosphoric acid (PA)-doped polybenzimidazole proton exchange membranes has progressed at a notably slow pace over the past few decades, primarily because of challenges such as the leaching of PA, plasticization effects, and the poisoning of critical components by free PA. Herein, a novel solid-state proton conductor, phosphoric acid-in-clay electrolyte (PA@halloysite nanotubes (HNTs)), is proposed, which features a 3D proton conduction network. This solid-state conductor partially replaces liquid PA, alleviating the problem of PA leaching. It exhibits strong interaction with PA (close to PA–PA binding energy), achieving a remarkable proton conductivity of 85.81 mS cm−1 at 180°C/0% relative humidity (RH). By incorporating PA@HNTs into grafted poly(2,5-benzimidazole) (g-ABPBI) via in situ polymerization, a composite membrane with outstanding performance is successfully developed. At a PA@HNTs content of 5 wt.%, the proton conductivity of composite membranes reached 0.080 and 0.127 S cm−1 at 90 °C/98% RH and 180 °C/0% RH, respectively. This performance is attributed to the large amount of PA contained in PA@HNTs, which establishes a dense hydrogen-bonding network, facilitating ultrafast proton transport via the combined “packed-acid mechanism” and “Grotthuss mechanism.” The PA@HNTs/g-ABPBI membrane provides a promising strategy for fuel cell operation over a wide-temperature range.